Composite proton exchange membrane and preparation method thereof

By introducing a composite coating structure of polyvinyl alcohol and perfluorosulfonic acid resin into the proton exchange membrane, the existing perfluorosulfonic acid membrane has solved the problems of high swelling rate and poor hydrolysis stability at high temperatures, and the mechanical properties, hydrolysis stability and proton conductivity of the composite proton exchange membrane have been improved.

CN119650777APending Publication Date: 2025-03-18HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411809482.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing perfluorosulfonic acid film has high swelling rate and poor hydrolysis stability at high temperatures, which limits its application in hydrogen fuel cells and other fields.

Method used

The composite proton exchange membrane structure is adopted, including a base film, a first coating and a second coating. The first coating and the second coating both contain polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA). Through the synergistic effect of polyvinyl alcohol and perfluorosulfonic acid resin, the proton conduction performance and chemical stability of the membrane are improved.

Benefits of technology

The mechanical properties and hydrolytic stability of the composite proton exchange membrane at high temperatures are achieved, while maintaining excellent proton conductivity and hydrogen barrier properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650777A_ABST
    Figure CN119650777A_ABST
Patent Text Reader

Abstract

The invention discloses a composite proton exchange membrane and a preparation method thereof, the composite proton exchange membrane comprises a base membrane, a first coating and a second coating, the first coating and the second coating are coated on two sides of the base membrane, the first coating comprises polyvinyl alcohol and perfluorinated sulfonic acid resin, and the second coating comprises polyvinyl alcohol and perfluorinated sulfonic acid resin. The thickness of the composite proton exchange membrane is 20-80 [mu] m, the thickness of the first coating is 2-38 [mu] m, and the thickness of the second coating is 2-38 [mu] m. According to the invention, the base membrane is used as a supporting material, relatively high mechanical properties are provided, a proton transmission channel is provided through the polyvinyl alcohol composite perfluorosulfonic acid, and extremely strong hydrogen bond interaction exists between molecules and in molecules of polyvinyl alcohol, so that the membrane has excellent proton conduction performance, and the performance of the membrane is improved. Meanwhile, due to the introduction of polyvinyl alcohol, the perfluorosulfonic acid and the base membrane have good binding capacity. The barrier property of the composite proton exchange membrane on hydrogen permeation is synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery separators, and in particular relates to a composite proton exchange membrane and a preparation method thereof. Background Art

[0002] Among all clean energy sources today, hydrogen energy and fuel cell systems seem to be the best solution to deal with energy dependence and greenhouse gas emissions. 2 As fuel, hydrogen energy is converted into electrical energy under the action of catalyst, and the only waste discharged is H 2 O, without any other carbon-containing pollutants. Therefore, hydrogen fuel cells are considered to be the ultimate energy source for mankind and a valuable option for solving climate warming and balancing energy needs.

[0004] Perfluorosulfonic acid membranes are widely used in the fields of proton exchange membranes, water electrolysis, chlor-alkali industry, etc. due to their excellent proton conductivity and good mechanical properties. However, their inherent disadvantages, such as high swelling rate at high temperature and poor hydrolysis stability, have also hindered their further development. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a composite proton exchange membrane.

[0006] Another object of the present invention is to provide a slurry.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A composite proton exchange membrane comprises: a base membrane and a first coating layer and a second coating layer coated on both sides of the base membrane, wherein the water contact angle on the surface of the base membrane is 40-65°, wherein the first coating layer comprises: polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA), wherein the second coating layer comprises: polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA), wherein in the first coating layer, the ratio of polyvinyl alcohol (PVA) to perfluorosulfonic acid resin (PFSA) is (0.5-1):(0.8-5) by weight, and in the second coating layer, the ratio of polyvinyl alcohol (PVA) to perfluorosulfonic acid resin (PFSA) is (0.5-1):(0.8-5) by weight.

[0009] In the above technical solution, the thickness of the composite proton exchange membrane is 20-80 μm, the thickness of the first coating is 2-38 μm, and the thickness of the second coating is 2-38 μm.

[0010] In the above technical solution, the ratio of the perfluorosulfonic acid resin (PFSA) in the first coating layer to the perfluorosulfonic acid resin (PFSA) in the second coating layer is (0.5-1.5): (0.5-1.5) by mass.

[0011] In the above technical solution, the base film, the first coating layer and the second coating layer have the same area.

[0012] In the above technical solution, in the first coating layer, the ratio of polyvinyl alcohol (PVA) to perfluorosulfonic acid resin (PFSA) is preferably (0.5-1): (2.5-3.5) by mass, and in the second coating layer, the ratio of polyvinyl alcohol (PVA) to perfluorosulfonic acid resin (PFSA) is preferably (0.5-1): (2.5-3.5) by mass.

[0013] In the above technical solution, the thickness of the composite proton exchange membrane is preferably 51-53 μm, the thickness of the first coating layer is preferably 17.5-19.5 μm, and the thickness of the second coating layer is preferably 17.5-19.5 μm.

[0014] In the above technical solution, the base film is a hydrophilic film, and the method for obtaining the hydrophilic film is: soaking the PE film or PP film in sulfuric acid for 2 to 6 hours, washing it with water for 3 to 5 times, and drying it to obtain the hydrophilic film.

[0015] In the method for obtaining a hydrophilic membrane, the concentration of sulfuric acid is 2 to 5 mol / L.

[0016] In the method for obtaining a hydrophilic membrane, the drying temperature is 60-80°C and the drying time is 1-2 hours. The method for preparing the above-mentioned composite proton exchange membrane comprises: casting a first slurry on a substrate, placing a base membrane on the first slurry, heating for the first time, obtaining a first coating on the lower surface of the base membrane, casting a second slurry on the upper surface of the base membrane, heating for the second time, obtaining a second coating on the upper surface of the base membrane, and post-processing to obtain a composite proton exchange membrane, wherein the first slurry and the second slurry are the same or different, and both the first slurry and the second slurry comprise: polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA), and the post-processing comprises soaking in sulfuric acid and hydrogen peroxide in sequence.

[0017] In the above technical solution, the temperature of the first heating is 60-90° C. and the time is 0.5-1.5 h.

[0018] In the above technical solution, the second heating includes: first drying at 60-90°C for 8-12 hours, and then drying at 110-130°C for 1-3 hours.

[0019] In the above technical solution, the post-treatment includes: first soaking in sulfuric acid at 60-90°C for 0.5-1.5h, then soaking in hydrogen peroxide at 60-90°C for 0.5-1.5h, washing, and drying.

[0020] In the post-treatment method, the concentration of the sulfuric acid is 0.5 to 1.2 mol / L.

[0021] In the post-treatment method, H 2 O 2 The concentration is 2.5~3.5wt%.

[0022] In the post-treatment method, the washing includes: first washing with water at room temperature, and then soaking in water at 60 to 90° C. for 0.5 to 1.5 hours.

[0023] A slurry comprises polyvinyl alcohol (PVA), perfluorosulfonic acid resin (PFSA) and a solvent, wherein the ratio of the polyvinyl alcohol (PVA) to the perfluorosulfonic acid resin (PFSA) is (0.5-1): (0.8-5) by weight.

[0024] In the above technical solution, the solid content of the slurry is 3-10wt%.

[0025] In the above technical solution, the solvent is one or a mixture of N-methylpyrrolidone (NMP), dimethyl sulfoxide and dimethylformamide.

[0026] The preparation method of the above-mentioned slurry includes: mixing a polyvinyl alcohol (PVA) solution and a perfluorosulfonic acid (PFSA) solution until they are uniform to obtain a slurry, wherein the polyvinyl alcohol (PVA) solution is a mixture of polyvinyl alcohol (PVA) powder and a first solvent, and the perfluorosulfonic acid (PFSA) solution is a mixture of perfluorosulfonic acid resin (PFSA) powder and a second solvent, and the ratio of polyvinyl alcohol (PVA) in the polyvinyl alcohol (PVA) solution to perfluorosulfonic acid resin (PFSA) in the perfluorosulfonic acid (PFSA) solution is (0.5-1): (0.8-5) by weight.

[0027] In the above technical solution, a polyvinyl alcohol (PVA) solution and a perfluorosulfonic acid (PFSA) solution are mixed and stirred at a speed of 400 to 600 r / min at 20 to 30° C. for 0.5 to 2 hours until they are uniform.

[0028] In the above technical scheme, the method for obtaining a polyvinyl alcohol (PVA) solution is: mixing polyvinyl alcohol (PVA) powder and a first solvent until uniform to obtain a polyvinyl alcohol (PVA) solution, wherein, by mass, the ratio of the polyvinyl alcohol (PVA) powder to the first solvent is (8 to 15): (85 to 92).

[0029] In the above technical solution, the first solvent is one or a mixture of N-methylpyrrolidone (NMP), dimethyl sulfoxide and dimethylformamide.

[0030] In the above technical solution, polyvinyl alcohol (PVA) powder and the first solvent are mixed and stirred at 60 to 110° C. at a speed of 400 to 500 r / min for 2 to 6 hours until they are uniform.

[0031] In the above technical scheme, the method for obtaining a perfluorosulfonic acid (PFSA) solution is: mixing a perfluorosulfonic acid resin (PFSA) powder and a second solvent until uniform to obtain a perfluorosulfonic acid (PFSA) solution, wherein the ratio of the perfluorosulfonic acid resin (PFSA) powder to the second solvent is (2 to 5.5): (94.5 to 98) by mass.

[0032] In the above technical solution, the second solvent is one or a mixture of N-methylpyrrolidone (NMP), dimethyl sulfoxide and dimethylformamide.

[0033] In the above technical solution, the perfluorosulfonic acid resin (PFSA) powder and the second solvent are mixed and stirred at 140-160° C. at a speed of 400-600 r / min for 2-6 hours until they are uniform.

[0034] Application of polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA) to synergistically improve the adhesion of the separator.

[0035] Application of polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA) to synergistically improve the hydrolytic stability of the membrane.

[0036] The application of polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA) to synergistically improve the hydrogen barrier performance of the membrane.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention uses a base film as a supporting material and a good carrier to provide higher mechanical properties, and provides a proton transmission channel by compounding polyvinyl alcohol (PVA) with perfluorosulfonic acid (PFSA). Polyvinyl alcohol (PVA) contains a large number of hydrogen bonds, and polyvinyl alcohol (PVA) molecules have extremely strong hydrogen bond interactions between molecules and within molecules, and then interact with perfluorosulfonic acid (PFSA), so that the diaphragm has excellent proton conduction performance, providing good proton conductivity for the diaphragm, and polyvinyl alcohol (PVA) is used as a cross-linking agent, and its introduction makes perfluorosulfonic acid (PFSA) and base film have good binding ability, aiming to further improve proton conductivity and chemical stability. The synergistic effect of polyvinyl alcohol (PVA), perfluorosulfonic acid (PFSA) and hydrophilic membrane makes the composite proton exchange membrane have excellent barrier properties to hydrogen permeation. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a photo of the composite proton exchange membrane prepared in Example 2;

[0040] Figure 2 This is a SEM of the composite proton exchange membrane prepared in Example 2;

[0041] Figure 3 This is the SEM of the PFSA membrane prepared in Comparative Example 1;

[0042] Figure 4 It is a hydrogen permeation test diagram of a membrane electrode formed by the composite proton exchange membrane of Example 2 and a membrane electrode formed by a standard membrane at a scanning rate of 4 mV / s;

[0043] Figure 5 is the water contact angle of PE film;

[0044] Figure 6 is the water contact angle of the hydrophilic membrane. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0046] The information related to the raw materials described in the following examples is as follows:

[0047] Perfluorosulfonic acid resin (powder), purity 98%, Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;

[0048] PVA (powder), purity 99%, MacLean Chemical Reagent;

[0049] N-Methylpyrrolidone (NMP), purity 99.5%, Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd.;

[0050] PE film, thickness 16μm.

[0051] The models and manufacturers of the equipment involved in the following embodiments and comparative examples are as follows:

[0052] Contact angle tester, MANUZL24464-7, Swiss Baioulin;

[0053] Scanning electron microscope, Sigma 300, Carl Zeiss, Germany;

[0054] Japan Shimadzu stretching machine, AGS-X (100N);

[0055] Electrochemical workstation, CHI660E, Shanghai Chenhua Instrument Co., Ltd.

[0056] In the following examples, the method for obtaining a hydrophilic membrane is as follows: PE membrane is immersed in sulfuric acid for 4 hours (the concentration of sulfuric acid is 3 mol / L), washed with deionized water for 4 times, and dried in an oven at 70° C. for 1.5 hours to obtain a hydrophilic membrane.

[0057] The test method in the following embodiments is as follows:

[0058] Hydrolytic stability value: The diaphragm with a mass of Wo (g) after pre-drying is placed in deionized water at 80°C and soaked for 48 hours. The immersed diaphragm is taken out and dried at 80°C for 8 hours. The mass is tested to be Wt (g). The hydrolytic stability value Wc is calculated by the following formula:

[0059]

[0060] Water absorption rate: Dry the membrane in an oven at 80℃±2℃ for 24 hours. After drying for 24 hours, measure the mass of the membrane as m0 (g). Then soak the membrane in distilled water at 80℃ for 8 hours. Use filter paper to remove water on the surface of the membrane. Measure the mass of the membrane within 30 seconds as m1 (g). The water absorption rate Δm is calculated by the following formula:

[0061]

[0062] Mechanical properties: The diaphragm was made into a rectangular strip with a length of 65 mm and a width of 15 mm. A universal tensile testing machine was used with a tensile speed of 5 mm / min and an original gauge length of 20 mm. The mechanical properties were calculated by the following formula:

[0063] σ 1 =p / (b×d), where σ1 is tensile strength (MPa), p is maximum load (N), b is width of rectangular spline (mm), d is thickness of rectangular spline (mm), and thickness is measured by thickness meter.

[0064] Proton conductivity test: carried out at a temperature of 25° C. and a humidity of 100% RH.

[0065] Diaphragm adhesion: Cut the diaphragm into a shape of 25mm×60mm, stick 3M tape on the diaphragm, and use a Japanese Shimadzu stretching machine to tear the 3M tape and the diaphragm apart. The force used is the diaphragm adhesion.

[0066] High temperature swelling rate test: Dry the diaphragm in an oven at 80℃±2℃ for 24 hours and then test its volume V 1 Then, the dried membrane was immersed in distilled water at 80°C for 24 hours and its volume was tested as V 2 , the swelling ratio Vc is calculated by the following formula:

[0067] Vc=(V 2 -V1 ) / V 1 ×100%.

[0068] Fuel cell hydrogen permeability test: First, use a slurry crusher to evenly disperse the catalyst (Pt / C) (the catalyst (Pt / C) was purchased from Shengernuo Energy Mall, JM 20% platinum carbon), and then use a homogenizer to evenly disperse 1.65g of the evenly dispersed catalyst, 0.35g of 5% Nafion solution and 8g of isopropanol to obtain a first mixed solution, and finally use an ultrasonic sprayer to load the first mixed solution on the diaphragm, and use a hot press to press the diaphragm loaded with the catalyst and carbon paper (carbon paper manufacturer: Japan Toray, model: TGP-H-060) to obtain a membrane electrode (the diaphragm is one of the composite proton exchange membrane and the standard membrane prepared in Example 2, and the membrane electrode is one of the membrane electrode formed by the composite proton exchange membrane of Example 2 and the membrane electrode formed by the standard membrane). On a fuel cell test bench (manufacturer: Beit New Energy, model: NBT-PEM-100W), an electrochemical workstation CHI660E was used to test the hydrogen permeation current of the membrane electrode (MEA) using linear sweep voltammetry (LSV). Within a voltage range of 0.4 V, the hydrogen permeation current was measured at 4 mV s -1 The disturbance voltage was applied at a dynamic scan rate of 1.5 s, and H was introduced into the anode of the fuel cell test bench (the anode provided in the fuel cell test bench) at a flow rate of 200 sccm. 2 (100% RH), N2 was introduced into the cathode of the fuel cell test bench (the cathode provided in the fuel cell test bench) at a flow rate of 200 sccm. 2 (100% RH). The standard membrane is a purchased standard sample, manufacturer: Shengernuo Energy Mall, model: SMEA1223.

[0069] In the tests of hydrolysis stability, water absorption, mechanical properties, proton conductivity and high-temperature swelling rate, the membrane is one of the composite proton exchange membranes prepared in Examples 1 to 6, the PFSA membrane prepared in Comparative Example 1, the PVA&PFSA membrane prepared in Comparative Example 2, and the PFSA&PE membrane prepared in Comparative Example 3.

[0070] Examples 1 to 6

[0071] A method for preparing a composite proton exchange membrane comprises: in the same container, casting a first slurry on a glass plate, placing a base film (hydrophilic membrane) on the first slurry, heating in an oven at 80°C for 1 hour, obtaining a first coating with a thickness of A μm on the lower surface of the base film, casting a second slurry on the upper surface of the base film, first drying in an oven at 80°C for 10 hours, then heating to 120°C, drying at 120°C for 1.5 hours, obtaining a second coating with a thickness of B μm on the upper surface of the base film, and post-processing to obtain a composite proton exchange membrane with a thickness of C μm, wherein the first slurry and the second slurry are the same, the first coating comprises: polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA), and the second coating comprises: polyvinyl alcohol (PVA) and perfluorosulfonic acid resin (PFSA). Fluorosulfonic acid resin (PFSA), in the first coating, the ratio of polyvinyl alcohol (PVA) to perfluorosulfonic acid resin (PFSA) is X, in the second coating, the ratio of polyvinyl alcohol (PVA) to perfluorosulfonic acid resin (PFSA) is Y, in the first coating and the second coating The ratio of perfluorosulfonic acid resin (PFSA) is Z, and the post-treatment is: first soaking in 60°C sulfuric acid (sulfuric acid concentration is 1 mol / L) for 1 hour, then soaking in 80°C hydrogen peroxide (hydrogen peroxide concentration is 3wt%) for 1 hour, washing (first washing with deionized water at room temperature, then soaking in 80°C water for 1 hour), and finally drying at 60°C for 12 hours.

[0072] The preparation method of the above-mentioned first slurry / second slurry includes: mixing a polyvinyl alcohol (PVA) solution and a perfluorosulfonic acid (PFSA) solution, stirring at a speed of 450 r / min for 1.5 hours at 25°C until uniform, to obtain a first slurry / second slurry, wherein the ratio of polyvinyl alcohol (PVA) in the polyvinyl alcohol (PVA) solution to perfluorosulfonic acid resin (PFSA) in the perfluorosulfonic acid (PFSA) solution is W, and the solid content of the slurry is Mwt% (actual test value).

[0073] The method for obtaining a polyvinyl alcohol (PVA) solution is as follows: polyvinyl alcohol (PVA) powder and a first solvent are mixed, and stirred at 90°C and a speed of 450 r / min for 3 hours until uniform, to obtain a polyvinyl alcohol (PVA) solution, wherein the ratio of the polyvinyl alcohol (PVA) powder to the first solvent is 10:90 by mass, and the first solvent is N-methylpyrrolidone (NMP).

[0074] The method for obtaining a perfluorosulfonic acid (PFSA) solution is as follows: mixing a perfluorosulfonic acid resin (PFSA) powder and a second solvent, stirring at 150° C. and a speed of 450 r / min for 4 hours until uniform, to obtain a perfluorosulfonic acid (PFSA) solution, wherein the ratio of the perfluorosulfonic acid resin (PFSA) powder to the second solvent is 5:95 by mass, and the second solvent is N-methylpyrrolidone (NMP).

[0075] The values ​​of A, B, C, X, Y, Z, W and M are shown in Table 1.

[0076] Table 1

[0077]

[0078] Comparative Example 1

[0079] A method for preparing a PFSA membrane comprises: casting 60 g of the perfluorosulfonic acid (PFSA) solution in Example 1 on a glass plate, placing the PFSA solution in an oven and drying it at 80° C. for 10 h, heating it to 120° C., drying it at 120° C. for 1.5 h, soaking it in 60° C. sulfuric acid (with a concentration of 1 mol / L) for 1 h, and then soaking it in 80° C. hydrogen peroxide (with a concentration of 3 wt %) for 1 h, taking it out, first washing it with deionized water at room temperature, and then soaking it in water at 80° C. for 1 h, taking it out and drying it at 60° C. for 12 h, to obtain a PFSA membrane with a thickness of 38 μm.

[0080] Comparative Example 2

[0081] A method for preparing a PVA&PFSA membrane comprises: casting 60 g of the first slurry in Example 2 on a glass plate, placing it in an oven and drying it at 80°C for 10 hours, heating it to 120°C, drying it at 120°C for 1.5 hours, soaking it in 60°C sulfuric acid (with a concentration of 1 mol / L) for 1 hour, and then soaking it in 80°C hydrogen peroxide (with a concentration of 3 wt%) for 1 hour, taking it out, first washing it with deionized water at room temperature, and then soaking it in water at 80°C for 1 hour, taking it out and drying it at 60°C for 12 hours to obtain a PVA&PFSA membrane with a thickness of 40 μm.

[0082] Comparative Example 3

[0083] A preparation method of a PFSA&PE membrane comprises: casting 30 g of the perfluorosulfonic acid (PFSA) solution in Example 1 on a glass plate, placing a hydrophilic membrane, heating in an oven at 80°C for 1 hour, obtaining a coating A on the lower surface of the hydrophilic membrane, casting the same amount of the perfluorosulfonic acid (PFSA) solution in Example 1, first drying in an oven at 80°C for 10 hours, then heating to 120°C, drying at 120°C for 1.5 hours, obtaining a coating B on the upper surface of the hydrophilic membrane, and post-treating: soaking in sulfuric acid (concentration of 1 mol / L) at 60°C for 1 hour, then soaking in hydrogen peroxide (concentration of 3 wt%) at 80°C for 1 hour, taking out, first washing with deionized water at room temperature, then soaking in water at 80°C for 1 hour, taking out and drying at 60°C for 12 hours, to obtain a PFSA&PE membrane with a thickness of 55 μm.

[0084] The test parameters of the composite proton exchange membranes prepared in Examples 1 to 6, the PFSA membrane prepared in Comparative Example 1, the PVA&PFSA membrane prepared in Comparative Example 2, and the PFSA&PE membrane prepared in Comparative Example 3 are shown in Table 2 (the water absorption rate is preferably in the range of 45-55%).

[0085] Table 2

[0086]

[0087]

[0088] It can be seen from Table 2 that among Examples 1 to 6, the composite proton exchange membrane prepared in Example 2 exhibits excellent mechanical properties and hydrolytic stability, and has the best proton conductivity (proton conductivity), water absorption rate and swelling rate parameters. By comparing Comparative Examples 1 to 3, it can be seen that the PFSA diaphragm prepared in Comparative Example 1 has lower mechanical properties and poorer hydrolytic stability. By Comparative Examples 1 and 2, it can be seen that the introduction of PVA effectively improves the mechanical properties (tensile strength) and hydrolytic stability of the diaphragm. By Comparative Examples 1 and 3, it can be seen that the introduction of a hydrophilic membrane can greatly improve the mechanical properties and hydrolytic stability of the diaphragm, but the hydrophilic membrane does not have a proton transport carrier, which will correspondingly reduce the proton conductivity. When the hydrophilic membrane is also introduced, the proton conductivity of Examples 1 to 3 is slightly affected, proving that the present invention achieves the advantages of good mechanical properties, high proton conductivity, good water absorption and good hydrolytic stability through the synergistic effect of PVA, PE and PFSA. At the same time, after the introduction of PVA, PFSA and PE have good adhesion and good bonding, so that the membrane adhesion of the composite proton exchange membrane is higher, and the swelling rate of the membrane is greatly reduced, proving that the stability of the membrane is highly improved. The results of the hydrogen permeation test prove that the composite proton exchange membrane of the present invention has excellent hydrogen barrier properties.

[0089] When the slurry in Example 2 is coated on one side of a PE film / hydrophilic film, the formed diaphragm will be severely curled after drying, which affects the use.

[0090] Figure 1 This is a photo of the composite proton exchange membrane prepared in Example 2. Figure 2 This is the SEM of the composite proton exchange membrane prepared in Example 2. Figure 3 This is the SEM of the PFSA membrane prepared in Comparative Example 1. Figure 4 The membrane electrode ( Figure 4 "PFSA & 16μmPE") and standard membrane electrode ( Figure 4 The hydrogen permeation test diagram of the "Standard Sample" in the figure at a scan rate of 4mV / s. Figure 5 Contact angle test of PE film. Figure 6 For hydrophilic membrane ( Figure 6 Contact angle test of "hydrophilic PE film").

[0091] pass Figure 2 and Figure 3 From the SEM, it can be seen that the surface flatness of the PFSA membrane of Comparative Example 1 is poor, while the surface of the composite proton exchange membrane prepared in Example 2 is smoother.

[0092] pass Figure 4 It can be seen that the membrane electrode formed by the standard membrane has a large current density in the hydrogen permeation test, reaching 8.5mA / cm 2 The main reason is that hydrogen permeates the diaphragm and reacts with the anode to form a path, resulting in a large current density. The membrane electrode prepared by the composite proton exchange membrane of Example 2 has a lower current density of only 2 mA / cm 2 , which proves that the amount of hydrogen passing through the composite proton exchange membrane of Example 2 is small, so the composite proton exchange membrane of the present invention has excellent hydrogen barrier performance.

[0093] pass Figure 5 and Figure 6 It can be seen that the water contact angle of the PE film is 88.65°, and the hydrophilic film ( Figure 6 The water contact angle of the "hydrophilic PE film" is 44.35°.

[0094] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A composite proton exchange membrane, characterized in that: include: A base film and a first coating and a second coating applied on both sides of the base film, wherein the first coating includes polyvinyl alcohol and perfluorosulfonic acid resin, and the second coating includes polyvinyl alcohol and perfluorosulfonic acid resin. In the first coating, the ratio of polyvinyl alcohol to perfluorosulfonic acid resin is (0.5-1):(0.8-5) by weight, and in the second coating, the ratio of polyvinyl alcohol to perfluorosulfonic acid resin is (0.5-1):(0.8-5) by weight.

2. The composite proton exchange membrane according to claim 1, characterized in that: The thickness of the composite proton exchange membrane is 20-80 μm, the thickness of the first coating is 2-38 μm, and the thickness of the second coating is 2-38 μm.

3. The composite proton exchange membrane according to claim 1, characterized in that: In terms of mass fractions, the ratio of the perfluorosulfonic acid resin in the first coating layer to the perfluorosulfonic acid resin in the second coating layer is (0.5-1.5): (0.5-1.5).

4. A method for preparing the composite proton exchange membrane according to any one of claims 1 to 3, comprising: The first slurry is cast on a substrate, a base film is placed on the first slurry, and a first coating is obtained on the lower surface of the base film by heating for the first time. The second slurry is cast on the upper surface of the base film, and a second coating is obtained on the upper surface of the base film by heating for the second time. A composite proton exchange membrane is obtained by post-treatment. The first slurry and the second slurry are the same or different. The first slurry and the second slurry both include: polyvinyl alcohol and perfluorosulfonic acid resin. The post-treatment includes soaking in sulfuric acid and hydrogen peroxide in sequence, and the water contact angle of the base film surface is 40 to 65°.

5. A slurry, characterized in that: include: The polyvinyl alcohol, the perfluorosulfonic acid resin and the solvent are present in a ratio of (0.5-1) to (0.8-5) by weight.

6. The slurry according to claim 5, characterized in that The solid content of the slurry is 3-10wt%.

7. The method for preparing the slurry according to claim 5 or 6, characterized in that: include: The polyvinyl alcohol solution and the perfluorosulfonic acid solution are mixed until uniform to obtain a slurry, wherein the polyvinyl alcohol solution is a mixture of polyvinyl alcohol powder and a first solvent, and the perfluorosulfonic acid solution is a mixture of perfluorosulfonic acid resin powder and a second solvent. The ratio of the polyvinyl alcohol in the polyvinyl alcohol solution to the perfluorosulfonic acid resin in the perfluorosulfonic acid solution is (0.5-1):(0.8-5) by weight.

8. The preparation method according to claim 7, characterized in that: In terms of weight percentage, the ratio of polyvinyl alcohol powder to the first solvent is (8-15): (85-92); in terms of weight percentage, the ratio of perfluorosulfonic acid resin powder to the second solvent is (2-5.5): (94.5-98); the first solvent is a mixture of one or more of N-methylpyrrolidone, dimethyl sulfoxide and dimethylformamide; the second solvent is a mixture of one or more of N-methylpyrrolidone, dimethyl sulfoxide and dimethylformamide.

9. The application of polyvinyl alcohol and perfluorosulfonic acid resin to synergistically improve the adhesion of diaphragms.

10. Application of polyvinyl alcohol and perfluorosulfonic acid resin to synergistically improve the hydrolysis stability and / or hydrogen barrier properties of the diaphragm.